ANALISIS PENGARUH ESG, LEVERAGE DAN ASSET EFFICIENCY TERHADAP SUSTAINABLE GROWTH RATE - Amini, Aulia Fadhilla; Yulianti, Retno (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study analyzes the influence of Environmental, Social, and Governance (ESG), Leverage, and Asset Efficiency on the Sustainable Growth Rate (SGR) of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The method used is multiple linear regression with 352 observational data from 111 companies. The results indicate that ESG and Leverage do not have a significant effect on SGR, whereas Asset Efficiency has a positive and significant effect on SGR. These findings suggest that ESG implementation in Indonesia remains uneven and is more compliance-driven rather than a growth-oriented strategy. Meanwhile, high leverage does not enhance SGR, implying that companies in this sector rely more on internal financing. Conversely, asset efficiency is proven to be a key factor in driving sustainable growth. This study is expected to provide insights for companies, investors, and regulators regarding the factors influencing sustainable growth.